Pengaruh Kualitas, Harga, kepuasan dan Citra Merek terhadap Keputusan Pembelian Produk Kecantikan - Cut Devi Maulidasari; Damrus Damrus; Chairiyaton Chairiyaton (universitas teuku umar, 2023)
In the midst of an increasingly advanced civilization, various companies are required to continue to innovate and maintain stability in order to be able to continue to exist in society and be able to compete in the business world. One of the businesses that continues to grow rapidly after the Covid-19 pandemic and has succeeded in dominating the domestic market to date is the sales-related industry that offers a variety of beauty products. In deciding to buy a product, potential customers have certain criteria. Research using qualitative research methods. Several factors drive consumer purchasing decisions, such as the quality of products marketed that do not contain harmful substances, the brand image attached to these products, and affordable product prices.Keywords: Quality, Price, Brand Image, Purchase Decision, Beauty Products